Effectiveness of Art Therapy on Cognitive Function of Older People with Dementia: A Systematic Review and Meta-Analysis - Jessica, Jessica; Lestari, Made Diah (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Asia currently bears the highest global burden of dementia, with 22.9 million cases—more than double the figures reported in Europe and the Americas. Given this catastrophic figure and the disadvantages of dementia for older people and caregivers, intervention focuses on prevention and maintaining cognitive function and well-being is needed. This study explores the effectiveness of Art Therapy on maintaining cognitive function and decelerating cognitive declines for older people with dementia in Asia. A systematic literature review and meta-analysis were conducted to evaluate the cognitive outcomes of art therapy interventions among older adults with dementia in Asia. In doing so, we meticulously selected and reviewed a total of 242 publications, and analysed 5 papers which addressed the poses of research aims. The review examined intervention characteristics, demographic data, and cognitive outcome measures, while meta-analysis using Hedges’ g was conducted to determine effect sizes. Art therapy involves numerous activities, such as drawing, colouring, music, collage-making, and reminiscence therapy applies a holistic approach, and typically facilitated by qualified professionals. The interventions demonstrated a holistic and structured approach aimed at enhancing psychological and cognitive well-being. The meta-analysis revealed a statistically significant overall effect on cognitive function (Hedges’ g = 0.586, p < .001), indicating that art therapy can meaningfully improve cognitive performance in older adults with dementia. The robustness of this finding was supported by a high Fail-safe N (n = 2341), suggesting strong resistance to publication bias. This study highlights compelling evidence that art therapy is an effective intervention for supporting cognitive health among older adults with dementia in Asia. Despite certain limitations—such as small sample size, short intervention durations, and lack of stratified analysis by dementia severity—the findings underscore the practical relevance of integrating art therapy into individual and community-level care. Future research should emphasize long-term follow-ups, standardized measures, and broader demographic representation to enhance the generalizability and impact of findings. For the practical implication, art therapy as a cognitive intervention can be applied to individual private practices and community activities for older people